Writing Ability of Description in Students of XI Grade at Vocational School - Basyaroh Purbania; Muhammad Rohmadi; Budhi Setiawan (Universitas Sebelas Maret, 2019)
This study aims to describe ability, results percentage, difficulties faced, and how to overcome students' difficulties in writing description compositions seen from the aspects of content, organization, effective sentence mastery, vocabulary, and mechanics in class XI AP1 SMK Batik 2 Surakarta. This study is a descriptive qualitative using a case study approach. The sampling technique used in this study is purposive sampling. The data sources in this study are documents (students’ description composition) and informants (teachers and students). Data collection techniques are carried out by document analysis and in-depth interviews. Data validity is done by data triangulation techniques, theories, and informant reviews. Data analysis techniques use interactive models, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the study are as follows. The ability results to be included in the category pretty good with vulnerable grades of 61-75. Furthermore, the results percentage of each aspect included the content aspect of 19%, the organizational aspect of 22%, the effective sentence mastery aspect by 16%, the vocabulary aspect by 24%, and the mechanical aspect by 19%. The influence of the writing description composition ability is caused by the difficulties faced by students in writing, namely: difficult to express ideas, difficult to develop sentences, difficult to determine good and right spelling, and difficult to concentrate. The solutions are: create an outline, look for sources of inspiration, use the enhanced spelling handbook, and more time to study (writing practice).